AC electrokinetics of conducting microparticles: A review. (August 2016) - Ramos, Antonio; García-Sánchez, Pablo; Morgan, Hywel
Abstract: This paper reviews both theory and experimental observation of the AC electrokinetic properties of conducting microparticles suspended in an aqueous electrolyte. Applied AC electric fields interact with the induced charge in the electrical double layer at the metal particle–electrolyte interface. In general, particle motion is governed by both the electric field interacting with the induced dipole on the particle and also the induced-charge electro-osmotic (ICEO) flow around the particle. The importance of the RC time for charging the double layer is highlighted. Experimental measurements of the AC electrokinetic behaviour of conducting particles (dielectrophoresis, electro-rotation and electro-orientation) are compared with theory, providing a comprehensive review of the relative importance of particle motion due to forces on the induced dipole compared with motion arising from induced-charge electro-osmotic flow. In addition, the electric-field driven assembly of conducting particles is reviewed in relation to their AC electrokinetic properties and behaviour. Graphical Abstract: Highlights: Experimental behaviour and theory of metal microparticles are compared. Particle motion is due to electrical forces on induced charges in the double layer. Characteristic time is the RC time for charging the metal/electrolyte double layer. Electric-field driven assembly of conducting particles is reviewed.